Minimally Invasive Management of Two Separated Dens Invaginatus Oehler’s Type I and II: A Case Report: Minimally invasive management of Dense invagination - Naqibeiranvand, Mohammad; Nasrabadi, Navid; Jahanshahi, Niloofar (Iranian Endodontic Journal, 2025)
Treating coronal dens invaginatus (CDI) with pulp infection typically involves the removal of the invaginatus, which increases the risk of fracture and perforation, compromising tooth structure. Minimally invasive endodontic management of coronal dens invaginatus is highly recommended. This case report presents the management of a 19-year-old female patient with a permanent maxillary lateral incisor exhibiting two distinct dens invaginatus anomalies. Cone-beam computed tomography (CBCT) was used to assist in the diagnosis of tooth morphology and canal location. CBCT confirmed that the buccally positioned orifice was classified as Oehlers Type II, while the one with a palatally positioned orifice corresponded to Oehlers Type l. The pulp and periapical diagnosis of this tooth was pulpless and an infected root canal system with chronic apical periodontitis according to Abbott classification. The pulp chamber was carefully accessed with minimal intervention, and the root canals were explored under magnification. All root canals were prepared using EDMax rotary files, followed by irrigation with sodium hypochlorite (NaOCl). Calcium hydroxide medication was also applied. Root canal obturation was performed using the warm vertical compaction, employing AH-Plus sealer in combination with thermosplasticized gutta-percha. After 6 and 12 months, the patient showed healing of the periapical region, with the absence of symptoms and normal dental function. Favorable radiographic and clinical findings were observed during both follow-up sessions. At the 18-month follow-up, the lesion was completely healed.